Calculation of a cylindrical surface that ensures a constant thrust or a constant amount of pressure of a particle of material moving through it at a constant speed - Pylypaka, S. F.; Nesvidomin, A. V. (Energy and Automation, 2023)
There are known studies in which the movement of material particles along gravitational surfaces is considered. The speed of movement along the curve in such cases is variable. However, in agricultural machines, there may be cases where a particle moves along a surface at a constant speed. In this case, in addition to the force of gravity, the force of traction acts on the particle.The purpose of the study is the calculation of a cylindrical surface that provides a constant traction force or a constant pressure value of a material particle moving along it at a constant speed.Curves were found along which a particle moving at a constant speed will exert a constant pressure or the active traction force will be constant.Equations have been found and curves have been constructed that ensure a constant force of traction or a constant amount of pressure of a material particle moving along a curve at a constant speed.These curves will retain their properties only if the value of the calculated speed is strictly observed. This is explained by the fact that in the equations of the curves, the speed value is squared, so even a slight deviation from the calculated one will cause a significant deviation of the expected results.Key words: material particle, cylindrical surface, weight force, traction force, speed